A vueltas con la descolonización: propuestas para algunas conceptualizaciones coloniales - Goikolea-Amiano, Itzea (Historiografías, 2020)
In light of the discussions on the legacies of colonialism which are recently taking place among scholars and civil society, this article suggests some theoretical-methodological tools to study the colonial past in a critical and “decolonial” way. We suggest to envision that category as a complex construction, in the shaping of which the colonised subjects, epistemologies, and socio-political structures played an important role. Building on a variety of works, we advance the usefulness of making the heterogeneity of perspectives visible and of making historical and spatial comparisons to avoid essentialisms. We also draw on some empirical examples from colonial Morocco related to gender and the “desacralization of history”. Keywords Colonialism, decolonial, Morocco, Islam, gender.